2010
DOI: 10.1002/pon.1620
|View full text |Cite
|
Sign up to set email alerts
|

A systematic narrative review of the studies on structured child‐centred interventions for families with a parent with cancer

Abstract: This review showed the lack of valid psychosocial preventive intervention methods focusing on children with parental cancer and highlighted the need of intervention research with controlled study designs and long follow-up periods. However, an intervention method should be easy to train and applicable to the clinical practice of healthcare professionals. By refining the practice-based experiences with scientific research evidence it is possible to move to the next level in providing psychosocial support and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 29 publications
2
70
0
1
Order By: Relevance
“…This intervention confirms the previous studies about the importance of an open communication to support children to face with cancer's diagnosis [5,10,[14][15][16]. The project highlights the advantages of direct engagement of children in the communication of the parent's illness to improve the relationships within the family.…”
Section: Discussionsupporting
confidence: 85%
“…This intervention confirms the previous studies about the importance of an open communication to support children to face with cancer's diagnosis [5,10,[14][15][16]. The project highlights the advantages of direct engagement of children in the communication of the parent's illness to improve the relationships within the family.…”
Section: Discussionsupporting
confidence: 85%
“…Problems such as disordered sleeping, compulsive behavior, and anxiety lasted longer [22] while uncertainty and helplessness decreased [21,45]. Although other reviews have concluded that the impact of parental cancer on later functioning cannot be determined due to insufficient evidence [65], one considered study found that negative emotional reactions were mostly unrelated to later functioning [45] which was reflected in a separate 12-month study [66]. This study was not included in this review as it failed to meet criteria due to considering children above 18 years.…”
Section: Impact Of Cancermentioning
confidence: 98%
“…Finally, it is also important for clinicians to provide help for those in need. In this respect, the results of a recent literature review are encouraging, indicating that family interventions can have positive impacts on adolescents' psychosocial well-being, lead to positive changes in cancer-related worries, and decrease distress symptoms (Niemela, Hakko, & Rasanen, 2010).…”
Section: Clinical Levels Of Psychological Distressmentioning
confidence: 95%